Health and criminal justice system involvement among African American siblings - Amber L. Beckley; Rohan H. Palmer; Michael Rocque; Keith E. Whitfield (Elsevier, 2019)
Importance: Health disparities between African Americans and Whites have persisted in the United States. Researchers have recently hypothesized that the relatively poor health of African Americans may be caused, in part, by African American overrepresentation in the criminal justice system. Objectives: To test the hypothesis that criminal justice system involvement is associated with poor health and greater health risk when controlling for unobserved family factors through a discordant sibling design. Methods: Subjects were drawn from the Carolina African American Twin Study of Aging (CAATSA). Criminal conviction records were extracted from North Carolina's Department of Public Safety. Six measures of health and one measure of health risk were analyzed. The health of convicted respondents was compared to that of unrelated non-convicted respondents matched on childhood and demographic factors ("matched sample"). Convicted respondents were also compared to non-convicted siblings ("discordant sibling sample"). Results: The matched sample included 134 CAATSA respondents. On average, convicted CAATSA respondents, compared to matched non-convicted respondents, were in worse health. Convicted respondents had worse mean self-reported health, worse lung function, more depressive symptoms, and smoked more. The discordant sibling sample included 74 respondents. Convicted siblings and non-convicted siblings had similar self-reported health, depressive symptoms, and smoking. In general, non-convicted siblings were in worse health than non-convicted respondents from the matched sample, implying that poor health runs in families. Conclusions: This study provided preliminary evidence that some of the association between a criminal record and poor health is confounded by family factors. Though more research is needed to support these results, the study suggests that criminal involvement may not be associated with the surfeit of health problems observed among African Americans. The criminal justice system, nonetheless, could be used to decrease the health disparity. Keywords: Health disparity, criminal justice system, discordant sibling design, offender health